2007
DOI: 10.1088/0029-5515/47/7/008
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced breaking of equilibrium flux surfaces in the W7AS stellarator

Abstract: Abstract. Calculations are presented for two shots in the W7AS stellarator which differ only in the magnitude of the current in the divertor control coil, but have very different values of experimentally attainable β (〈β〉 ≈ 2.7% vs. 〈β〉 ≈ 1.8%). Equilibrium calculations find that a region of chaotic magnetic field line trajectories fills approximately the outer 1/3 of the cross section in each of these configurations. The field lines in the stochastic region are calculated to behave as if the flux surfaces are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…However, for regions with stochastic magnetic fields (of interest for tokamaks with ergodic limiters and for the edge regions of high-β stellarators), the condition is conventionally interpreted to mean that the pressure profile is flattened. Nevertheless, nonvanishing pressure gradients are observed in both experiments and simulations [75], so a more refined description is required.…”
Section: Application Of Renormalization To the Theory Of Stochastic Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for regions with stochastic magnetic fields (of interest for tokamaks with ergodic limiters and for the edge regions of high-β stellarators), the condition is conventionally interpreted to mean that the pressure profile is flattened. Nevertheless, nonvanishing pressure gradients are observed in both experiments and simulations [75], so a more refined description is required.…”
Section: Application Of Renormalization To the Theory Of Stochastic Mmentioning
confidence: 99%
“…Reiman et al [75] observed that flattening need not occur in the presence of weak flows or an anisotropic pressure tensor. Furthermore, they outlined a hybrid analytical/numerical procedure wherein the magnetic-field configuration could be calculated without explicit reference to those effects.…”
Section: Application Of Renormalization To the Theory Of Stochastic Mmentioning
confidence: 99%
“…In such cases the magnetic well even reformed when β was increased. While in W7-AS, again at reduced field, the equilibrium limit has been reached [17], in W7-X, owing to a small Shafranov shift, also the equilibrium limit should not curtail the value of <β> = 5 %.…”
Section: Reliable Operationmentioning
confidence: 95%
“…In addition to ion temperature profiles, which are derived from the Doppler width of the resonance line w, it will therefore also be possible to measure profiles of the electron temperature from the satellite-to-resonance-line ratios. The second objective is to provide theoretical support for the data analysis, using the stellarator equilibrium reconstruction codes STELLOPT and PIES [15][16][17][18][19]. Equilibrium reconstruction is a necessary first step in doing theoretical analysis, such as transport and stability calculations.…”
Section: Objectivesmentioning
confidence: 99%
“…In three-dimensional equilibria, there is an issue of equilibrium flux surface loss, so that the equilibrium itself is of interest for determining the extent of pressure-driven flux surface stochastization. Equilibrium reconstruction for the W7AS stellarator indicated that, in some cases, equilibrium flux surface loss played an important role in limiting the achievable β [15,16]. For these calculations, the STELLOPT reconstruction code [15,17] was first used to obtain an equilibrium reconstruction assuming nested flux surfaces.…”
Section: Objectivesmentioning
confidence: 99%